Application of Probability Analysis of Rainfall for Design of Continuous Contour Trenches, Contour Bund and Waste Weirs in Bankura - Mishra, Purnima; Mazumdar, A; Babu, R Ravi (Journal of Agricultural Engineering, 2006)
Continuous Contour Trenches (CCTs) along with pasture/afforestation on barren hillocks (locally known as dungri) and Contour bunding along with afforestation as land use in wastelands (locally known as Tand/Danga) are the most popular soil and water conservation measures adopted in different watershed development projects implemented in Bankura district of West Bengal. The results of probability analysis of rainfall of Bankura can be effectively applied for the better design of these measures. In the present study, the predicted 1 day maximum rainfall for the desired return period using best fit Log Pearson Type - III probability distribution was usee for the better design of CCTs on a barren hillock, covering an area of about 10 ha and contour bund and waste weir system in wasteland covering an area of 14.17 ha falling in RK-35 and Kashibedia micro-watersheds, respectively, in Bankura district of West Bengal.